2020
DOI: 10.1590/1806-9282.66.8.1093
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile of pediatric patients with chronic rheumatic diseases - a retrospective analysis

Abstract: SUMMARY AIM To describe the prevalence of dyslipidemia in children and adolescents with autoimmune rheumatic diseases (ARDs), particularly juvenile idiopathic arthritis (JIA), juvenile systemic lupus erythematosus (jSLE), and juvenile dermatomyositis (JDM). METHODS Retrospective cross-sectional study conducted in the pediatric rheumatology outpatient clinic. We evaluated 186 children and adolescents between the ages of 5 and 19 years. The medical records were reviewed for the following data: demographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The present study showed that dyslipidemia affected more than three-quarters of JIA patients, with the predominance of borderline-low HDL-c based on classical lipid profile. Similar results were found in a retrospective study published by our research group [23]. We observed a higher frequency of increased LDL-c, NHDL-c, and Apo B in the systemic subtype than the polyarticular subtype.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that dyslipidemia affected more than three-quarters of JIA patients, with the predominance of borderline-low HDL-c based on classical lipid profile. Similar results were found in a retrospective study published by our research group [23]. We observed a higher frequency of increased LDL-c, NHDL-c, and Apo B in the systemic subtype than the polyarticular subtype.…”
Section: Discussionsupporting
confidence: 92%
“…A retrospective cross-sectional study of 2020 by Rodrigues et al. ( 52 ), aimed to describe the prevalence of dyslipidemia in children and adolescents with autoimmune diseases (ARDs), such as JSLE. They studied 186 children and adolescents between the ages of 5 and 19 years old and found dyslipidemia in 128 patients (68.8%), the most common being low HDL-C (74 patients, 39.8%).…”
Section: Resultsmentioning
confidence: 99%
“…An examination of blood lipids showed that children with SLE had obvious lipid metabolism disorders in the early stage, and they could be divided into the following types: increased serum TC level, increased serum TG level, increased serum LDL level, and decreased serum HDL level [ 15 ]. Some cross-sectional analytical studies found dyslipidemia rates of about 50%–85% in children with SLE [ 16 , 17 ]; however, no epidemiological studies have examined the blood lipid levels in children with LN. The incidence of dyslipidemia in children with LN in the current study was 89.2%, which was significantly higher than that in children without LN.…”
Section: Discussionmentioning
confidence: 99%